J.C. Bancroft Davis papers - Davis, J. C. Bancroft (John Chandler Bancroft), 1822-1907.
Bound volumes of correspondence, diaries, journals, reports, printed matter, and other papers relating primarily to Davis's diplomatic career, especially his role in the Alabama claims dispute with Great Britain following the U.S. Civil War. Documents his work as an American correspondent for the London Times and U.S. Supreme Court reporter; and his part in negotiations between the U.S. and Great Britain relating to Central American affairs.
Jurist, diplomat, journalist, and court reporter.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: United States. -- Supreme Court; Times (London, England); Alabama claims; Foreign correspondents -- United States; Law reporters -- United States; Central America -- History -- 1821-1951.; Great Britain -- Foreign relations -- United States; United States -- Foreign relations -- Great Britain; United States -- History -- Civil War, 1861-1865 -- Claims; Diplomats; Journalists; Jurists; Law reporters